2020
DOI: 10.1007/s10585-020-10028-0
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel node tumor burden in prediction of prognosis in melanoma patients

Abstract: Recent data have demonstrated no survival benefit to immediate completion lymph node dissection (CLND) for positive sentinel node (SN) disease in melanoma. It is important to identify parameters in positive SNs, which predict prognosis in melanoma patients. These might provide prognostic value in staging systems and risk models by guiding high-risk patients' adjuvant therapy in clinical practice. In this retrospective study of university hospital melanoma database we analyzed tumor burden and prognosis in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
(46 reference statements)
2
7
0
Order By: Relevance
“…In our opinion, CLND adds prognostic information as the status of non-sentinel nodes is an independent prognostic feature, as we have demonstrated not only in the present analysis but also previously (6,11) . Therefore, CLND not only improves regional relapse-free survival (as demonstrated by the results of the MSLT-II) but also provides physicians with useful prognostic information (6)(7)(8) .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In our opinion, CLND adds prognostic information as the status of non-sentinel nodes is an independent prognostic feature, as we have demonstrated not only in the present analysis but also previously (6,11) . Therefore, CLND not only improves regional relapse-free survival (as demonstrated by the results of the MSLT-II) but also provides physicians with useful prognostic information (6)(7)(8) .…”
Section: Discussionsupporting
confidence: 86%
“…Another study analyzing 104 SN positive patients who underwent CLND demonstrated that the 5year melanoma specific survival for CLND-negative patients was 5 years as compared to 3.69 years in CLND positive patients. In this analysis, clinico-pathological parameters such as diameter of tumor deposit, distribution of metastatic focus within the sentinel node, ulceration and number of metastatic sentinel nodes were evaluated and the investigators found that TB >4 mm and multifocal metastatic disease within the sentinel node were the most important variables that allowed an accurate prognostic stratification of patients (11) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these trials, the results of which might lead to abandon the practice of CLND, had some limitations. First, retrospective series produced varied results and were subject to a considerable risk of select bias; next, there were differences in clinic-pathologic features of the patient cohorts between centers; moreover, most patients, enrolled in these studies, had a low-volume nodal tumor burden [ 5 , 7 , 9 11 ]. In the end, international guidelines such as those issued by the National Comprehensive Cancer Network, recommend to discuss with the patient the benefit of CLND mainly based on the risk of harboring additional lymph node metastatic disease.…”
Section: Introductionmentioning
confidence: 99%